Optical properties of pure and erbium-doped tin dioxide thin films fabricated by sol-gel technique / Shahida Hanum Kamarullah ...[et al.] - Kamarullah, Shahida Hanum; Yahya, Norihan; Mohamed, Ruziana; Aziz, Madzlan (2012)
In this study, the pure tin oxide (SnO2) and erbium doped tin dioxide thin films have been prepared on glass substrate using sol-gel technique. The surface morphology, microstructure and properties of the films are characterized by using Field Emission Scanning Electron Microscope, X-ray diffraction and Photoluminescence. It was found that the particles in the Sn02 thin films have the diameter ranging from 20 to 44 nm with spherical morphology. Sn02 thin films have tetragonal structure with prominent peaks corresponding to (1 1 0), (1 0 1) and (2 I I) crystal lattice planes. The photoluminescence (PL) emission peaks of Sn02:Er3+ corresponding to the characteristic H - I transitions between the energy levels of Er3+ ion.